Implementation of the Prehospital Stroke Scale as a Stroke Attack Screening Tool for the High Risk Community - Kustanti, Cecilya; Widyarani, Linda (Universitas Airlangga, 2020)
Introduction: The process of changing a person into adolescence is a very important process where in adolescence, the process of finding the identity of a teenager is ongoing, looking for self-identity, trying new things, and social processes such as having a group of friends who he thinks have one hobby with him. Commonly referred to as